(untitled) (REMUNOM, 2024)
The paper "Gestational Diabetes: Risks, Diagnosis, and Management During Pregnancy in Primary Health Care Centers" analyzes the situation of gestational diabetes (GD), a metabolic disorder that affects pregnant women and can lead to serious complications for both mother and fetus, such as preeclampsia and fetal macrosomia. The research examines the main risk factors for Gestational Diabetes, such as obesity, advanced maternal age, and family history of diabetes. Additionally, it discusses diagnostic methods, with a focus on the oral glucose tolerance test (OGTT) for early identification. The management of Gestational Diabetes in Basic Health Units (UBS) is examined from a multidisciplinary perspective, involving the supervision of various health professionals, including obstetricians, endocrinologists, and nutritionists. The approach involved research and analysis of studies to evaluate the effectiveness of diagnosis and treatment in the Primary Health Care Center, aiming to ensure a healthy pregnancy. The paper emphasizes the importance of unified strategies in GD management and the need for more efficient protocols in caring for pregnant women, thus mitigating the risks to both mother and fetus.